The Effect of Inflation and Interest Rates on Investment Decision Making Through Gold Prices of Indonesian Sharia Bank Customers - Wicaksono, Anang Eko; Rahmawati, Imelda Dian (Amkop Management Accounting Review (AMAR), 2025)
The purpose of this study is to determine the effect of inflation on gold prices, to determine the effect of interest rates on gold prices, to determine the effect of inflation on investment decision making, to determine the effect of interest rates on investment decision making, to determine the effect of gold prices on investment decision making, to determine the effect of gold prices on investment decision making, to determine the gold price mediates the relationship between inflation and investment decision making and to determine the gold price mediates the relationship between interest rates and investment decision making. This study employs quantitative methods and collects primary data. The data analysis technique used in this study to empirically test the hypotheses developed is Partial Least Squares (PLS). The results of the study indicate that inflation affects gold prices, interest rates affect gold prices, inflation affects investment decision making, interest rates affect investment decision making, gold prices affect investment decision making, gold prices mediate the relationship between inflation and investment decision making, and gold prices mediate the relationship between interest rates and investment decision making.